Congenital corneal clouding: A case series - Malik, Sushma; Lichade, Vinaya Manohar; Sajjan, Shruti M.; Gandhi, Prachi Shailesh; Rathod, Darshana Babubhai; Wade, Poonam Abhay (Indian Journal of Child Health, 2019)
Congenital corneal clouding often causes diagnostic dilemma; hence, detailed evaluation and timely intervention are required to decrease the morbidity. Various genetic, developmental, metabolic, and idiopathic causes of congenital corneal clouding include Peters anomaly, sclerocornea, birth trauma, congenital glaucoma, mucopolysaccharidosis, and dermoids. We report a case series of four neonates with congenital corneal clouding admitted in our neonatal intensive care unit, over 5 years. Two cases were of Peters anomaly, one each of primary congenital glaucoma and glaucoma secondary to congenital rubella.